Періодизація пізнього палеоліту України - Залізняк, Л.Л. (Археологія і давня історія України, 2010)
Стаття є спробою узагальнення тривалих зусиль
кількох поколінь дослідників в галузі періодизації та
культурного поділу пізнього палеоліту України. Короткий очерк периодизации верхнего палеолита Украины является попыткой подведения итогов
столетним усилиям нескольких поколений украинских ученых в указанной области палеолитоведения.
Современный уровень наших знаний позволяет выделить четыре фазы культурно-исторического развития верхнего палеолита Украины: раннюю (40—
27 тыс. л. н.), среднюю (27—19 тыс. л. н.), позднюю
(19—14 тыс. л. н.) и финальную (14—10 тыс. л. н.).
Периодизация частично коррелируется со стратиграфической схемой позднечетвертичных отложений
Украины Н.П. Герасименко (2004), в основе которой лежит схема М.Ф. Веклича. The article proposes a summary of centennial efforts
of several generations of scholars in the field of
periodization of the Upper Paleolithic of Ukraine.
The analysis of available data permits to distinguish
four phases of cultural and historical development
of the UP in Ukraine: early (40—27 Ka BP), middle
(27—19 Ka BP), late (19—14 Ka BP) and final (14—
10 Ka BP). This periodization is correlated, to a certain
extent, with the stratigraphic chart of Late Quaternary
deposits of Ukraine elaborated by N.P. Herasymenko,
Zh.M. Matviyishyna and P.F. Hozhyk and based on
M.F. Veklych’s chart.